It cannoli be murder - Bruns, Catherine (Bruns, Catherine. Italian chef mystery, 2020)
"Six months after her husband Dylan's death, Tessa Esposito is prepping for the grand opening of her new Italian restaurant, Anything's Pastable. Meanwhile her cousin Gabby is trying to increase traffic at her new bookstore. So when New York Times bestselling author, Preston Rigotta, agrees to a book signing, Tessa offers to lend a hand, catering a variety of sweet Italian treats for the occasion. But the signing soon takes a bitter turn when Preston's publicist and Gabby's old Harvest Park High rival arrives and exchanges sharp words with Gabby in front of the crowded store. Things get even worse when the publicist's lifeless body is discovered the next morning, with Tessa's biscotti in hand. Tessa decides she needs to track down a killer before her career ends on a sour note"--